Aspects of the ecology and reproductive biology of three cichlid fish species of Southern Lake Malombe (Malawi) - Jambo, Collins Mayeso (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1998)
The three major species Lethrinops ''pinkhead'', Otopharynx argyrosoma "red" and Copadichromis. cf virginalis which used to dominate the catches (by weight) of Lake Malombe in the past decade were investigated. In order to make rational recommendations regarding size and boundary of the existing sanctuary area (lightly fished), distribution and abundance, population structure and reproductive biology of the three species were related to habitat types of the southern part of the lake (south western side and south eastern side). Analysis of catch composition showed that species richness was higher in the south eastern side than in the south western side of the lake. Rare species such as Labeo mesops and Opsaridium microiepis were observed in the south eastern side and there was visual absence of such species in the south western side of the lake. The overall fish abundance was significantly greater in the south eastern side than in the south western side of the lake. In the south eastern side, the catch per unit effort (CPUE) was twice that of the south western side (P< 0.05). Seasonal fluctuations in CPUE were also prominent, with the highest peak occurring during September-October period. However, there was an indication of weak relationship among CPUE, phytoplankton biomass, temperature and water depth. The length-weight relationships revealed that growth of the three species closely followed the cubic law for isometric growth in both sides of the lake. Differences in regression coefficients between sides were not significant (ttest, P>0.05). The length-frequency distribution analysis revealed that the three species had the same growth rate regardless of habitat type. However, females grew faster than males. An investigation of reproductive biology showed that the three species have low fecundity and they are asynchronous spawners, with a breeding peak during August and September period. Furthermore, the length-fecundity relationships for L. ''pinkhead'', and 0. argyrosoma "red" indicated that fecundity was more closely related to length in the south eastern side than in the south western side. Based on the above characteristics of L. ''pinkhead'', 0. argyrosoma "red" and C. cf virginalis, and the substrate types, it was strongly suggested that the existing sanctuary (lightly fished) in the south eastern side of the lake could immediately be enlarged to conserve the fish stocks, favourable substratum and aquatic animals that may be of tourists concern.
Keywords: Cichlids -- Africa, East -- Lake Malombe; Cichlids -- Ecology